Implementasi Metode Dempster-Shafer Untuk Mendeteksi Penyakit Pada Anjing - Muhammad Zainuri Aziz; Nurul Hidayat; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Dogs are one of the most popular pets in the world. Dogs are easily attacked by disease. When the dogs are attacked by disease it will certainly cause certain symptoms. People who keep dogs mostly do not know the various diseases experienced by the dog. Implementation that can know the various diseases of dogs from the data of the symptoms experienced by the dog can be done, so that dog owners and veterinarians can be more easily to know the illness they suffered. In this application applied Dempster-Shafer method because this method was known from one of the same symptoms can be known more than one disease that exists. With this method also can overcome the problems. The accuracy of this system is 85.53% which means the system can run well because the result of the system closely matches the actual field facts.